Reactions to Sales Restrictions on Flavored Vape Products or All Vape Products Among Young Adults in the United States. Issue 3 (31st July 2021) - Posner, Heather; Romm, Katelyn F; Henriksen, Lisa; Bernat, Debra; Berg, Carla J
Abstract: Introduction: Despite increases in e-cigarette sales restrictions, support for sales restrictions and perceived impact on young adult use are unclear. Aims and Methods: We analyzed February-May 2020 data from a longitudinal study of 2159 young adults (ages 18–34; Mage = 24.75 ± 4.71; n = 550 past 30-day e-cigarette users) in six metropolitan areas (Atlanta, Boston, Minneapolis, Oklahoma City, San Diego, and Seattle). We examined support for e-cigarette sales restrictions and—among e-cigarette users—perceived impact of flavored vape product and all vape product sales restrictions on e-cigarette and cigarette use (and potential correlates; ie, e-cigarette/tobacco use, use-related symptoms/health concerns). Results: About 24.2% of e-cigarette users (and 57.6% of nonusers) supported (strongly/somewhat) sales restrictions on flavored vape products; 15.1% of e-cigarette users (45.1% of nonusers) supported complete vape product sales restrictions. If restricted to tobacco flavors, 39.1% of e-cigarette users reported being likely (very/somewhat) to continue using e-cigarettes (30.5% not at all likely); 33.2% were likely to switch to cigarettes (45.5% not at all). Considering complete vape product sales restrictions, equal numbers (~39%) were likely versus not at all likely to switch to cigarettes. Greater policy support correlated with being e-cigarette nonusers (adjusted R 2 [a R 2 ] = .210); among users, correlates included fewer days of use and greater symptoms and health concerns (a R 2 = .393). If such restrictions were implemented, those less likely to report continuing to vape or switching to cigarettes used e-cigarettes on fewer days, were never smokers, and indicated greater health concern (a R 2 = .361). Conclusions: While lower-risk users may be more positively impacted by such policies, other young adult user subgroups may not experience benefit. Implications: Young adult e-cigarette users indicate low support for e-cigarette sales restrictions (both for flavored products and complete restrictions). Moreover, if vape product sales were restricted to tobacco flavors, 39.1% of users reported being likely to continue using e-cigarettes but 33.2% were likely to switch to cigarettes. If vape product sales were entirely restricted, e-cigarette users were equally likely to switch to cigarettes versus not (~40%). Those most likely to report positive impact of such policies being implemented were less frequent users, never smokers, and those with greater e-cigarette-related health concerns. This research should be considered in future tobacco control initiatives.